Affective Abilities of Students in Elementary Schools in an Urban Community Environment - Delfiyan Widiyanto; Farikah Farikah; Jendriadi Jendriadi; Umi Rachmawati; Annisa Istiqomah (PT ARRUS Intelektual Indonesia, 2023)
Low affective competence is the cause of student behavior in elementary school. One of the problems faced by elementary school students in the city of Magelang is their attitudes that deviate from the norm, such as difficulty being managed both in class and at school, bad speech, behavior against teachers, and behavior that deviates from the norm. Students do not have sufficient affective abilities, which results in their tiresome behavior. This research aims to learn more about student deviation and the reduction of affective competence in schools located in the urban community of Magelang City. In addition, researchers will study further the reasons why students have low levels of affective abilities. It is hoped that this research can improve the quality of education and educate a golden generation with traits. To dig deeper into students' affective competence and the reasons behind it, this research uses a mixed type of research. The research location is SD Negeri Magersari 3 in Magelang City. In the first stage of data collection, observation and documentation questionnaires were used; in the second stage, interviews, documentation and observation are used. The results show that students' affective abilities in learning are very good, and the school environment is also very good. The shortcomings include three elementary school students who are considered to have low interest, seven students who are considered to have low caring affective competence, and one student who is considered to have a very low level of self-confidence.